(untitled) (Nordic Journal of African Studies, 2002)
The paper examined critically the various ways through which corruption had became institutionalized in Nigerian and its subsequent impact on political culture and behaviour on the one hand and its implications for development on the other hand. The paper hypothesized that the institutionalization of corruption leads to an overall change in the value-system and norms of behaviour in a society. This was eventually related exclusively to politics and the manifestations of corruption in the political arena were discussed. The paper poked at the whole scenario from the sociological perspective and the Durkheimian postulation that all behaviour is socially generated. And as such corruption should be seen largely as a social problem and not as emanating from individual dispositions. On the basis of the submission, some categorical imperatives were suggested in order to reduce the level of corruption. The paper concluded by saying that any social problem deserves societal attention and collective solution. The nation as such has the responsibility to educate, mobilize, socialize, enlighten and sensitise its citizens towards a tradition of honesty, excellence, truth, diligence, integrity, honour, reputation, good name and other moral virtues that will lead to the establishment of a new social order.